The relationship between the role of parents and the incidence of teenage pregnancy in Blimbing Village, Paciran District, Lamongan Regency - Kartikasari, Ratih Indah; Ummah, Faizatul; Wahyu, Deti Ilma (Jurnal Surya, 2022)
Introduction: Pregnancy at the age of teenagers between 14-19 years carries a heavy risk. From the initial survey data, there were 30 primigravida mothers (78.9%) pregnant in their teens (14-19 years). The purpose of this study was to determine the relationship between the role of parents and the incidence of pregnancy in adolescents.Methods: Analytical correlation with a cross-sectional approach, with a sample of some primi pregnant women in Blimbing Village, Paciran District, Lamongan Regency as many as 38 respondents who were taken by simple random sampling. Collecting data using a closed questionnaire, and tested with Coefficient Contingency.Results: The results showed that pregnant women who had less parental roles were almost entirely pregnant in their teens, namely 30 or (78.9%), while those who had sufficient parental roles were almost entirely pregnant at their teenage years, namely 14 or (36.8%). The results of the Coefficient Contingency test obtained a value of rs = 0.378 and p = 0.012 (p < 0.05) so that H0 is rejected, meaning that there is a relationship between the role of parents and pregnancy in adolescents.Conclusion: This study indicate that the role of parents is a very important factor in the incidence of pregnancy in adolescents, it is necessary to provide counseling and education to adolescents and parents about the impact and risks of the incidence of pregnancy in adolescence so that marriage does not occur at an early age and delays marriage. pregnancy in adolescents who are already married early.